Crianças transgêneras: educação e sociedade - Dias, Kaminski Zoz Daju (Universidade Federal de São Carlos, 2023)
The present study aimed to conduct a bibliographic survey on how issues relevant to the daily lives of LGBTQIA+ children and adolescents, particularly transgender individuals, in Brazilian schools are approached by academia. The descriptors used for the search on the CAFE Capes platform were: Transgender school; LGBTQIA+ school; Transgender education; LGBTQIA+ children and adolescents, and Transgender children. Sixty-seven works were selected, and ten were chosen based on the objectives of this study. The methodology employed was qualitative research, involving document analysis and bibliographic research. Together, these methods provided a rich search for documents, their analysis, comparisons, in-depth investigations, and questioning, to approach a conclusion on the topic. It is evident that, despite progress in our society and education, much still needs to be done to ensure a quality space for learning for our LGBTQIA+ children, especially transgender individuals, without subjecting them to such prejudiced acts of violence in these settings.
Transgender children: education and society
Keywords: Aprendizado; Ensino; Comunidade LGBTQIA+; Apprenticeship; Teaching; LGBTQIA+ community; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO